2020
DOI: 10.18103/mra.v8i10.2248
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Curcumin in COVID-19 Treatment and Prevention: A Global Health Perspective

Abstract: Turmeric (Curcuma Longa) has a near 4000-year history of extensive medical use in South Asia. Its main physiologically active phytochemical is curcumin (diferuloylmethane), derived from the rhizome of turmeric. Curcumin is a hydrophobic polyphenol with a diketone moiety connecting two phenoxy rings. It is widely available, and exerts systemic and pleiotropic effects via several key mechanisms. Most famously, it is known to inhibit pro-inflammatory pathways such as PI3k/akt/NF-kB activation. It is also a potent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 73 publications
0
8
0
Order By: Relevance
“…The thirty children are infected to post-COVID-19 Multisystem Infl ammatory Syndrome (MIS-C) in the control area. But it absolutely was interesting that under the 20 people showed as passive coronavirus carrier with absolute recovery in the 11-slum sample area, and it had been remarkable that no reinfection occurs within the middle and early cohort of all relations thanks to the consequences of biomedicine, TE or TMT, long-lasting potential immunity because of the presence of potential, effective and active phytochemical-constituents in curcumin of turmeric, etc., are signifi cantly active against COVID-19 [1,2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]28,29,33,35,37,40,41,[44][45][46][47][48][49][50][51][52][53][54][55][56]. So, this preventive treatment measures revealed that high-diluted-internal-potential-biomedicine, TE, or TMT, are highly effective in controlling diseases by boosting resistance against coronavirus with no side effects.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The thirty children are infected to post-COVID-19 Multisystem Infl ammatory Syndrome (MIS-C) in the control area. But it absolutely was interesting that under the 20 people showed as passive coronavirus carrier with absolute recovery in the 11-slum sample area, and it had been remarkable that no reinfection occurs within the middle and early cohort of all relations thanks to the consequences of biomedicine, TE or TMT, long-lasting potential immunity because of the presence of potential, effective and active phytochemical-constituents in curcumin of turmeric, etc., are signifi cantly active against COVID-19 [1,2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]28,29,33,35,37,40,41,[44][45][46][47][48][49][50][51][52][53][54][55][56]. So, this preventive treatment measures revealed that high-diluted-internal-potential-biomedicine, TE, or TMT, are highly effective in controlling diseases by boosting resistance against coronavirus with no side effects.…”
Section: Resultsmentioning
confidence: 99%
“…So, this preventive treatment measures revealed that high-diluted-internal-potential-biomedicine, TE, or TMT, are highly effective in controlling diseases by boosting resistance against coronavirus with no side effects. During the 2nd phase of the pandemic of the 11-slum area of Purba Bardhaman, the "Burdwan Green Haunter, and Students' Goal"-NGO, actively involved for awareness regarding the medication with covid-protocol, and that they also reported that the 2nd phase-COVID-19 reinfection within the slum from the 11th September 2020 to 17th July 2021, no active or severe COVID-19 middle-aged patient is shown within the 11-core-NGO-activity slum, except within the Aatagarh of Burdwan-II, where two MIS-C children of post-COVID-19 positive infection, and admitted within the hospital, and recovered, but out of 30, one died in another area [1,2,[6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]28,29,33,35,37,40,41,[44][45][46][47][48][49][50][51][52][53][54][55][56]. On the opposite hand, within the non-experimental control area (In Figure…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Wuhan, China on December 2019 for the first-time nCoV19 was discovered which was later on announced a pandemic by world health organization. Generally it is a respiratory disease, which also acts on other organ systems like cardiovascular system, kidneys as well as nervous system (Roberts et al, 2020). COVID-19 is 96.5% alike to bat coronavirus RaTG13, which means bats might be the host of the virus and recognized to be passed on via close proximity and air droplets (Babaei et al, 2020;Guo et al, 2020).…”
Section: Introductionmentioning
confidence: 99%